RETRACTED: lncRNA BZRAP1‐AS1 alleviates rheumatoid arthritis by regulating miR‐1286/COL5A2 axis - Junsong Zhu; Shaoheng Tu; Qunwei Qu (Immunity, Inflammation and Disease)
Abstract Background Dysregulation of BZRAP1‐AS1 was associated with immune statuses of cancer or Alzheimer's disease patients, yet little is known about its role in rheumatoid arthritis. Methods RT‐qPCR and western blot were applied to assess the expression of indicated expression. CCK‐8 and BrdU proliferation assays were used to measure the proliferation of RA‐HFLS. Apoptosis in RA‐HFLS was evidenced by the alteration of caspase‐3 activity and apoptosis‐related factors. ELISA was performed to detect IL‐6, IL‐1β, and TNF‐α level. Luciferase reporter, RIP, and pull‐down assays were used to confirm the BZRAP1‐AS1/miR‐1286/COL5A2 cascade predicted by bioinformatics analysis. Results BZRAP1‐AS1 and COL5A2 were downregulated in RA tissues and RA‐HFLS while miR‐1286 was amplified. Overexpression of BZRAP1‐AS1 reduced the RA‐HFLS proliferation, IL‐6, IL‐1β, and TNF‐α level and induced cell apoptosis while BZRAP1‐AS1 silence produced an opposite effect. Overexpression of BZRAP1‐AS1 reduced the miR‐1286 expression which in turn increased the COL5A2 expression, thereby relieving the excessive proliferation and limited apoptosis in RA‐HFLS. Conclusion Our findings suggested that BZRAP1‐AS1 sequestered miR‐1286 and reshaped the COL5A2 expression, thereby suppressed RA‐HFLS proliferation and inflammation, and triggered cell apoptosis, resulting in the attenuation of RA progression.